Temporal dynamics of quality of life and functional recovery In paediatric supracondylar humerus fractures: a prospective study - Taib, Mai Nurul Ashikin; Kamalanathan, Colin Komahen; Sharifudin, Mohd Ariff; A. Rahman, Laila Maisarah; Abu Bakar, Mohamad Zakwan Helmi; Awang, Mohd Shukrimi (Universiti Putra Malaysia Press, 2024)
Introduction: The trajectory of recovery following paediatric supracondylar humerus fractures (SCHF) remains uncertain, necessitating a comprehensive assessment of the quality of life (QOL) and functional status over time. Understanding the temporal dynamics of QOL and functional recovery is essential for optimizing rehabilitation strategies and support systems for affected children. This prospective study aims to investigate the temporal dynamics of QOL and functional recovery to optimize rehabilitation strategies. Methods: Forty children aged 6-12 years with SCHF were enrolled. Demographic data, including parental occupation, education levels, and household income, were collected. QOL was measured using the PedsQL 4.0™ Generic Core Scales, while functional outcomes were assessed using the Mayo Elbow Performance Index (MEPI) at 6-, 12-, and 24-week intervals post-injury. Results: QOL improved rapidly post-injury, correlating with functional outcomes. A significant recovery window occurred between 6 and 12 weeks, with marginal improvements thereafter. Children of average weight demonstrated better and quicker QOL recovery compared to overweight peers. Children with higher-educated parents experienced greater emotional struggles post-injury, while those from lower-income households exhibited better emotional coping mechanisms. MEPI results indicated significant improvements in functional recovery over the study period. Conclusion: Our study reveals a rapid recovery period between 6- and 12-weeks post-injury, with marginal improvements, thereafter, suggesting a potential recovery plateau. Identifying recovery plateaus and understanding the impact of various factors on outcomes will significantly influence resource allocation and family support systems in rehabilitation efforts.